Evolução da migração de partos para Aracaju, Sergipe, Brasil, 1970-1996 - Gurgel, Ricardo Queiroz (2003)
This study analyzes trends in the migration of childbirth from rural areas of Sergipe State, Brazil, to the capital city, Aracaju, from 1970 to 1996. Data on “mother’s place of residence” were obtained from mothers whose children were born in maternity hospitals in Aracaju in 1970, 1976, 1986, and 1996. Significant differences occurred in the proportion of mothers who resided outside of Aracaju but came there to give birth, especially from 1976 to 1986. This shift was stimulated by improvement of State highways and the granting of personal political favors in exchange for votes. Changes in the State hospital structure did not appear to have influenced the childbirth shift to Aracaju. There was a 134.6% increase in deliveries occurring in the State capital. There were also different trends among the various regions of the State, with some regional health districts displaying a downward trend in the number of deliveries from 1986 to 1996. It is urgent that more regional and hierarchical support be provided for childbirth and neonatal care in order to ensure quality assistance for pregnant women and their infants.